When COVID-19 is the invader and internal communication is the hero: Understanding the influence of internal communication on individual performance and evaluating the mediating role of perceived support - Daniel Roque Gomes; Patricia Lourenço; Neuza Ribeiro (Administrative Sciences, 2021)
Objective: The main objective of this study was to evaluate the impact of internal communication (IC) of organisations on the quality of the individual–organisation relationship, specifically with regard to the effects generated with respect to individual performance (IP) in a pandemic framework. In this sense, the study intends to evaluate the effects of IC on the employee's IP, having as a mediator perceived organisational support (POS). Methodology: To achieve the aforementioned objectives, a cross-sectional quantitative study was prepared, data for which were collected during a period of confinement that took place between 9 February and 15 March 2021. A total of 340 individuals of both sexes participated in the study. Genders were 67.6% female and 32.4% male, with ages ranging from 25 years to over 61 years, from all districts of Portugal and the Islands. Results: The main results obtained showed that IC was positively and significantly correlated with POS and also with IP, and that there was also a total mediation effect of POS in the relationship between IC and IP. Practical implications: These results seem to support the need for organisations to invest in their internal communication practices as a way of stimulating strong and fruitful relationships between workers and the organisation. Internal communication seems to be a relevant indicator for the management of proximity relationships with workers, especially in adverse contexts, like the ones experienced during the pandemic crisis. Well-developed internal communication supports and practices seem to be a valid path towards developing bonds leading to improved performance.
Keywords: 350; internal communication; perceived support; performance